Manajemen Rantai Pasokan (Supply Chain Management) dalam Meningkatkan Efisiensi dan Daya Saing Perusahaan - Safira, Muthia; Putri, Tri Anada; Hasanah, Fitri; Lusiana (Indo-MathEdu Intellectuals Journal, 2026)
Supply Chain Management (SCM) is a strategic approach that emphasises the integration and coordination of cross-functional business activities, ranging from the procurement of raw materials and the production process to the distribution of products to end consumers. This study aims to analyse the role of SCM in enhancing operational efficiency and corporate competitiveness amidst the challenges of globalisation and the accelerating digitalisation of the economy. The research method employed is a literature review using a descriptive-qualitative approach, involving a systematic search and analysis of textbooks, reputable national and international journal articles, and research reports relevant to the topic of SCM. Data were analysed by grouping findings based on aspects of supply chain integration, the utilisation of information technology, and collaboration among business partners. The results of the study indicate that the implementation of an integrated SCM is capable of improving a company’s operational performance through reduced lead times, lower logistics costs, increased flexibility, and improved service quality. Furthermore, the use of information technology and strategic partnerships among supply chain participants has proven to be a key factor in creating sustainable competitive advantage.